Bentuk-Bentuk Etika Komunikasi Dakwah dalam Perspektif Al-Qur’an - Handayani, Nur Annisa Tri; Jaya, Canra Krisna (Journal of Da'wah, 2024)
The Qur’an provides clear guidelines on communication ethics in da’wah, which include the principles of politeness, gentleness, honesty, wisdom, and patience. In carrying out the task of da’wah, every da’wah must adhere to these values to convey Islamic messages in an appropriate, civilized, and effective manner. This article aims to analyze the forms of da’wah communication ethics according to the perspective of the Qur’an, including politeness in speaking (Al-Baqarah: 83), gentleness in delivering messages (Thaha: 44), honesty and transparency (An-Nisa: 9), wisdom in da’wah (An-Nahl: 125), and patience in conveying the truth (Luqman: 17). We employ a literature review and analysis of the Qur’anic interpretation to comprehend the application of these principles in contemporary da’wah. The results of the study show that the Qur’an emphasizes the importance of effective, empathetic, and wise communication in efforts to spread Islamic teachings. The Qur’an serves as a crucial basis for modern da’wah practices that are more adaptable and contextual. The Qur’an provides complete guidance on the ethics of da’wah communication, which includes the principles of politeness, gentleness, honesty, wisdom, and patience